Communication Skills and Their Relation to Transferable Skills for Vocational High School Students - Suroto, Suroto; Pargito, Pargito; Sukirlan, Muhammad; Firdaus, Rangga; Winatha, I Komang; Rahmanto, Andi Adam; Rozak, Abdul (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2023)
One of the important abilities possessed by job seekers is transferable skills. The demands of the industry in fulfilling the workforce in the Industrial 4.0 era are more complex because they have to be adapted to hard skills and soft skills competencies. SMK is an important point in meeting the needs of industrial workers. The transferable skills developed are communication, cooperation, and discipline and responsibility. The aim is to analyze the development of transferable skills in productive learning at SMK and the absorption of soft skills by SMK students. This study uses a quantitative approach in which data processing is carried out using statistical methods. The type of research used in this study is the Quasi-Experimental method: Nonequivalent Control Group Designs. The researcher tries to find out the effect of the dependent variable and examines it retrospectively to establish causes, relationships, associations and their meaning. This research will be conducted on students of Agriculture Vocational Schools in Central Lampung . The results of this study indicate that communication skills really support the transferable skills of vocational students